Relevansi Hukum Kodrat Stoa terhadap Disrupsi Kecerdasan Buatan - Theo, Yohanes (Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
Artificial intelligence begins to be treated as a conscious entity; it can feel guilty, and provide improvements for more perfect results in the future. I raises the important question: is human life still secure? This article discusses the relevance of Stoic natural law in regard with the disruption of artificial intelligence. This research was designed as a literature review. In the midst of the progress of artificial intelligence, this article aims to discuss human nature from the perspective of Stoicism's human philosophical thought, especially one of nature. The Stoics were one of the academic schools in the Hellenistic era that specifically paid attention to the concept of nature. The core of their moral teachings is found in the imperative